Failure to Identify Somatic Mutations in Monozygotic Twins Discordant for Schizophrenia by Whole Exome Sequencing - Lyu, Nan (Chin Med J (Engl), 2016)
BACKGROUND: Schizophrenia (SCZ) is a severe, debilitating, and complex psychiatric disorder with multiple causative factors. An increasing number of studies have determined that rare variations play an important role in its etiology. A somatic mutation is a rare form of genetic variation that occurs at an early stage of embryonic development and is thought to contribute substantially to the development of SCZ. The aim of the study was to explore the novel pathogenic somatic single nucleotide variations (SNVs) and somatic insertions and deletions (indels) of SCZ. METHODS: One Chinese family with a monozygotic (MZ) twin pair discordant for SCZ was included. Whole exome sequencing was performed in the co-twin and their parents. Rigorous filtering processes were conducted to prioritize pathogenic somatic variations, and all identified SNVs and indels were further confirmed by Sanger sequencing. RESULTS: One somatic SNV and two somatic indels were identified after rigorous selection processes. However, none was validated by Sanger sequencing. CONCLUSIONS: This study is not alone in the failure to identify pathogenic somatic variations in MZ twins, suggesting that exonic somatic variations are extremely rare. Further efforts are warranted to explore the potential genetic mechanism of SCZ.